Twenty two years later: An updated checklist of Neotropical spider wasps (Hymenoptera: Pompilidae) - Fernández, Fernando; Rodriguez, Juanita; Waichert, Cecilia; Decker, Brenna; Pitts, James (Zootaxa, 2022)
Twenty two years after the first checklist of Neotropical Spider Wasps, a new list of genera and species is offered, including novelties in phylogeny and systematics, as well as reviews, synonyms and descriptions since the year 2000. Sixty three genera and 946 species of Pompilidae are listed.